1998
DOI: 10.3168/jds.s0022-0302(98)75889-8
|View full text |Cite
|
Sign up to set email alerts
|

Glucose Metabolism and Milk Yield of Cows Infused Abomasally or Ruminally with Starch

Abstract: The effect of ruminal or abomasal starch infusion on milk yield and glucose metabolism of early lactation cows was measured. Four cows were continuously infused in the rumen or abomasum with partially hydrolyzed starch (1500 g/d) or were not infused (control) for three 14-d periods during wk 4 to 12 postpartum. Milk yield averaged over 40 kg/d throughout the experiment. Milk and milk lactose yields tended to increase when starch was infused and DMI was decreased, regardless of the site of infusion. Starch infu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

16
61
6
6

Year Published

2004
2004
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 84 publications
(89 citation statements)
references
References 30 publications
16
61
6
6
Order By: Relevance
“…Concerning plasma NEFA levels, 13 [9, [60][61][62][63][64][65][66][67][68] out of 15 studies found an increase after feeding extra lipogenic nutrients. In contrast to studies where extra glycogenic nutrients were fed, 13 [60,61,66,[68][69][70][71][72][73] out of 14 reported studies found a decrease in plasma NEFA levels. Plasma BHBA levels increased after feeding extra lipogenic nutrients in five out of eight studies [68,69,74,75].…”
Section: Effect Of Lipogenic and Glycogenic Nutrients On Blood Metabomentioning
confidence: 83%
See 4 more Smart Citations
“…Concerning plasma NEFA levels, 13 [9, [60][61][62][63][64][65][66][67][68] out of 15 studies found an increase after feeding extra lipogenic nutrients. In contrast to studies where extra glycogenic nutrients were fed, 13 [60,61,66,[68][69][70][71][72][73] out of 14 reported studies found a decrease in plasma NEFA levels. Plasma BHBA levels increased after feeding extra lipogenic nutrients in five out of eight studies [68,69,74,75].…”
Section: Effect Of Lipogenic and Glycogenic Nutrients On Blood Metabomentioning
confidence: 83%
“…Plasma BHBA levels increased after feeding extra lipogenic nutrients in five out of eight studies [68,69,74,75]. Extra glycogenic nutrients were related to a decrease in plasma BHBA levels in eight out of nine reported studies [61,69,70,72,74,76]. Plasma glucose (10 out of 13 studies) and insulin (6 out of 9 studies) concentrations were decreased after feeding extra lipogenic nutrients and in almost all cases increased after feeding extra glycogenic nutrients (glucose 13 out of 14 studies; insulin 7 out of 8 studies) [8, 9, 60, 61, 64, 66-68, 70-72, 74, 76, 77].…”
Section: Effect Of Lipogenic and Glycogenic Nutrients On Blood Metabomentioning
confidence: 92%
See 3 more Smart Citations